Unsteady-state kinetic simulation of naphtha reforming and coke combustion processes in the fixed and moving catalyst beds; Catalysis Today; Vol. 220-222: International Symposium on Advances in Hydroprocessing of Oil Fractions (ISAHOF 2013) - Zagoruiko A. N. Andrey Nikolaevich; Belyi A. S. Alexander; Smolikov M. D. Mikhail; Noskov A. S. Alexander (2014, 2014)
Title screen